Mechanistic insights into the generation and control of Cl-DBPs during wastewater sludge chlorination disinfection process. (September 2022) - Zhang, Weijun; Dong, Tianyi; Ai, Jing; Fu, Qinglong; Zhang, Nan; He, Hang; Wang, Qilin; Wang, Dongsheng
Graphical abstract: Highlights: The microorganism E. coli in sludge was effectively inactivated by NaClO treatment. Lignin and N-compounds in sludge were major precursors for Cl-DBPs generation. N-compounds played the leading role in the generation of Cl-DBPs. Acidic condition prevented Cl-DBPs generation by lowering the N-compounds production. Abstract: Chlorination disinfection has been widely used to kill the pathogenic microorganisms in wastewater sludge during the special Covid-19 period, but sludge chlorination might cause the generation of harmful disinfection byproducts (DBPs). In this work, the transformation of extracellular polymeric substance (EPS) and mechanisms of Cl-DBPs generation during sludge disinfection by sodium hypochlorite (NaClO) were investigated using multispectral analysis in combination with Fourier transform ion cyclotron resonance mass spectrometry (FTICR-MS). The microorganism Escherichia coli ( E. coli ) was effectively inactivated by active chlorine generated from NaClO. However, a high diversity of Cl-DBPs were produced with the addition of NaClO into sludge, causing the increase of acute toxicity on Q67 luminous bacteria of chlorinated EPS. A variety of N-containing molecular formulas were produced after chlorination, but N-containing DBPs were not detected, which might be the indicative of the dissociation of –NH2 groups after Cl-DBPs generated. Additionally, the release of N-containing compounds was increased in alkaline environment caused by NaClO addition, resulted in more Cl-DBPs generation via nucleophilic substitutions. Whereas, less N-compounds and Cl-DBPs were detected after EPS chlorination under acidic environment, leading to lower cell cytotoxicity. Therefore, N-containing compounds of lignin derivatives in sludge were the major Cl-DBPs precursors, and acidic environment could control the release of N-compounds by eliminating the dissociation of functional groups in lignin derivatives, consequently reducing the generation and cytotoxicity of Cl-DBPs. This study highlights the importance to control the alkalinity of sludge to reduce Cl-DBPs generation prior to chlorination disinfection process, and ensure the safety of subsequential disposal for wastewater sludge.